2015
DOI: 10.1021/acs.nanolett.5b00155
|View full text |Cite
|
Sign up to set email alerts
|

Kondo Effect in a Neutral and Stable All Organic Radical Single Molecule Break Junction

Abstract: Organic radicals are neutral, purely organic molecules exhibiting an intrinsic magnetic moment due to the presence of an unpaired electron in the molecule in its ground state. This property, added to the low spin-orbit coupling and weak hyperfine interactions, make neutral organic radicals good candidates for molecular spintronics insofar as the radical character is stable in solid state electronic devices. Here we show that the paramagnetism of the polychlorotriphenylmethyl radical molecule in the form of a K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
147
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 131 publications
(155 citation statements)
references
References 36 publications
7
147
0
1
Order By: Relevance
“…We find that the normal state characteristics (and Kondo effect) of the molecular junctions are consistent with previous reports of the same molecule in completely gold break junctions [46] (see Supplemental Material for details [47]. Furthermore, from the linear conductance in the Kondo regime we estimate an asymmetry in the couplings (Γ L , Γ R ) to the leads of Γ L =Γ R ≈ 5 × 10 −4 .…”
supporting
confidence: 91%
“…We find that the normal state characteristics (and Kondo effect) of the molecular junctions are consistent with previous reports of the same molecule in completely gold break junctions [46] (see Supplemental Material for details [47]. Furthermore, from the linear conductance in the Kondo regime we estimate an asymmetry in the couplings (Γ L , Γ R ) to the leads of Γ L =Γ R ≈ 5 × 10 −4 .…”
supporting
confidence: 91%
“…In particular, the Kondo effect has been observed in low temperature (typically 10 K) experiments on single molecules under relatively large applied magnetic fields (typically several Tesla). 8,9 The effect is a consequence of spin correlation between the charge carriers in the contact and in the molecule. This interaction leads to a conductance characterized by a zero-bias resonance, which is sensitive to an applied magnetic field.…”
Section: Itroductionmentioning
confidence: 99%
“…A meticulous experimental determination of the magnetic anisotropy of the molecule would be even pos-sible, as done for instance in single molecule tunnel junctions based on organic molecules. 46,47 During the preparation of this manuscript S.T. Akin et al 22 reported XMCD measurements for Co 3 Bz + 3 cluster with null spin-magnetic moment.…”
Section: Final Remarksmentioning
confidence: 99%